Unusual presentation and management of spindle cell lipoma: A case report - Ralph Chalhoub; Fadi Sleilati (JPRAS Open, 2023)
Spindle cell lipoma is a benign tumor composed of mature adipocytes and uniform spindle cells, it does not exceed usually more than 2.5 cm and can be treated surgically and does not require wide surgical margins. It must be differentiated from liposarcoma and other malignant tumours and can be differentiated based on imaging and histological features. We report a case of 67-year-old male who developed a posterior thoracic mass more than 10 years ago, that grew recently, whose imaging features was suggestive of liposarcoma, and was treated as such.